Comparative evaluation of iodinated, nanoparticle-based, and gadolinium-based contrast agents in computed tomography for small animals - Julie van Krimpen Mortensen; Emil Svendborg Christensen; Amalie Littau; Nicoline Rosenkilde Kjaer; Sophie Arndt; Anne Skovsbo Clausen; Andreas Clemmensen; Andreas Kjaer (PLoS ONE, 2026)
Preclinical computed tomography (CT) is extensively used for anatomical reference and multimodal imaging, but the soft tissue contrast is poor compared to clinical CT. This hinders reliable organ delineation and segmentation in small-animal studies. We present a systematic evaluation of commonly used clinical iodinated and gadolinium-based contrast agents, together with a preclinical nanoparticle-based contrast agent. This evaluation aims to enhance soft-tissue boundary definition and in vivo visibility. The study consisted of two parts. First, phantom experiments were performed to assess the relationship between contrast-agent concentration and Hounsfield Unit (HU) across multiple dilutions and CT energy settings. Second, these findings were evaluated in vivo in mice to assess organ-level enhancement. Phantom measurements demonstrated a linear relationship between HU and concentration for all agents; however, at higher dilutions, contrast enhancement became indistinguishable from the background. In vivo, clinical iodinated and gadolinium-based agents administered intraperitoneal (IP) provided enhanced soft-tissue contrast by outlining abdominal organs, whereas the intravenously administered nanoparticle agent exhibited pronounced organ-specific accumulation. Overall, IP injection of clinical iodinated contrast agents offers a cost-effective and practical strategy for enhancing organ boundary visibility in preclinical CT. For longitudinal or organ-specific imaging studies, the preclinical nanoparticle-based contrast agent remains advantageous, as its cumulative uptake allows detection over extended periods and minimizes burden from multiple injections.